2019
DOI: 10.1016/j.jaci.2019.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones reduce asthma exacerbation in asthmatic patients with high PAI-1–producing genotypes

Abstract: Background: The 4G4G genotype of plasminogen activator inhibitor (PAI-1) is associated with increased plasma PAI-1 levels and poor asthma control. Previous studies suggest that soy isoflavones can reduce PAI-1 levels. Objective: We sought to investigate PAI-1 genotype-specific differences of the soy isoflavone response in asthma outcomes. Methods: A PAI-1 functional polymorphism (rs1799768, 4G5G) was characterized in subjects with poorly controlled asthma enrolled in a randomized clinical trial of soy isoflavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Previous studies report that elevated SERPINE1 levels are correlated with cellular senescence and the aging process ( Yamamoto et al, 2005 ; Kortlever et al, 2006 ; Eren et al, 2014 ). We have been studying the role of PAI-1 in the airway remodeling of asthma ( Cho et al, 2001 ; Jo et al, 2018 ; Cho et al, 2019 ). However, it has not been known about the role of PAI-1 in NP, especially in age-related roles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies report that elevated SERPINE1 levels are correlated with cellular senescence and the aging process ( Yamamoto et al, 2005 ; Kortlever et al, 2006 ; Eren et al, 2014 ). We have been studying the role of PAI-1 in the airway remodeling of asthma ( Cho et al, 2001 ; Jo et al, 2018 ; Cho et al, 2019 ). However, it has not been known about the role of PAI-1 in NP, especially in age-related roles.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that upregulation of plasminogen activator inhibitor‐1 (PAI‐1) leads to asthma exacerbations. Genistein is found to decrease the level of TGF‐β1‐induce‐PAI‐1 in the epithelial cells of the airways in asthmatic patients (Cho et al., 2019). In the study by Pintova et al, it has been reported that oral treatment with genistein prior to chemotherapy in metastatic colorectal cancer patients has significantly reduced chemotherapy‐related adverse events and was found to be safe and tolerable (Pintova et al., 2019).…”
Section: Clinical Significance Of Genistein With Respect To Recent Clinical Trialsmentioning
confidence: 99%
“…These consists of small double-stranded RNA fragments capable of triggering the degradation of a specific mRNA [7] and therefore ultimately capable of blocking the synthesis of certain proteins. Recently, the true efficacy of siRNA directed against particular targets, such as STAT6, PAI-1, and Syk for the treatment of asthma was demonstrated through appropriate in vitro and in vivo studies [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional therapies, therefore, are often associated with a series of limitations that have pushed the research towards the identification of new biological targets for treatment of the pathology. It has been seen that in individuals suffering from asthma there is overexpression of numerous genes and proteins, such as Signal Transducer and Activator of Transcription 6 (STAT6) [4], Plasminogen Activator Inhibitor-1 (PAI-1) [5], and Spleen Tyrosine Kinase (Syk) [6]. In particular, STAT6 regulates the T helper type 2 (Th 2 ) immune response, PAI-1 is associated with asthma severity because of its role in airway remodeling, while Syk is implicated as central immune modulator promoting allergic airway inflammation; thus, their inhibition could be an effective therapeutic approach in asthma.…”
Section: Introductionmentioning
confidence: 99%